PREPARATION OF PATIENTS WITH DIABETES MELLITUS AND COMPLETE EDENTULISM FOR DENTAL IMPLANT PLACEMENT (Journal of Multidisciplinary Sciences and Innovations, 2026)
This article discusses the clinical features of preparing patients with diabetes mellitus who have complete edentulism for dental implant placement. Special attention is given to the influence of diabetes on oral tissues, bone metabolism, and wound healing processes. The importance of controlling blood glucose levels, conducting comprehensive medical examinations, and eliminating inflammatory conditions in the oral cavity before implant surgery is emphasized. Modern diagnostic methods, including radiographic and three-dimensional imaging techniques, are highlighted as essential tools for evaluating bone structure and planning implant treatment. In addition, the role of oral hygiene, patient education, nutritional regulation, and interdisciplinary cooperation between dentists and medical specialists is discussed. Proper preoperative preparation significantly reduces surgical risks and improves the long-term success of implant-supported prosthetic rehabilitation in diabetic patients with complete tooth loss.